The Military Regime and Pakistan's Political And Administrative System: The Performance of Musharraf Regime in the First Year - Mahmood, Dr. Sohail (Journal of Political Studies, 2000)
As the Musharraf regime completes its first year in office, it faces a serious challenge on several fronts. Today, Pakistan's Political and administrative system is faced with grave systemic failures and structural faults. Since these faults remained prevalent for too long, the political and administrative systems have seriously malfunctioned as a results. The Musharraf regime inherited a very bad political and economic situation. The past eleven years of democracy (1988-1999) had certainly failed to deliver.